Bladder Cancer in Lebanon: An Updated Epidemiological Comparison with Global Regions and a Comprehensive Review of Risk Factors - Najla A. Lakkis MD, MPH; Mona H. Osman MD, MPH, MBA; Reem M. Abdallah MD; Nour M. Mokalled MD (Cancer Control)
Objectives This study aims to analyze urinary bladder cancer (UBC) incidence rates in Lebanon over a 12-year period (2005-2016) and compare them with rates in other countries. It also discusses UBC risk factors in Lebanon. Introduction Lebanon has one of the highest estimated age-standardized incidence rates (ASIRw) of UBC worldwide. Methods Data on UBC were obtained from the Lebanese national cancer registry for the years 2005-2016. The study calculated age-standardized incidence rates (ASIRw) and age-specific rates per 100 000 population. It also estimated the population attributable fractions of smoking, water pollution, and air pollution for UBC incidence in Lebanon in 2016. However, limited data precluded sensitivity analyses, potentially affecting the robustness of the estimates. Results During this period, UBC ranked as the third most common cancer in males (12.9% of all new cancer cases) and the eighth most common in females (2.8% of all new cancer cases), excluding non-melanoma skin cancer. The average ASIRw was 28.8 in men and 6.6 in women, placing Lebanon among the countries with the highest UBC incidence rates globally. UBC incidence rates increased with age. Estimates indicated that 46.4% of UBC cases in the Lebanese population were attributed to current smoking, 8.6% to water pollution with disinfection byproducts, and 6.0% to air pollution with PM2.5. Conclusion This study underscores the urgent need to mitigate UBC risk in Lebanon through tobacco control and by reducing exposure to preventable environmental and occupational risk factors, including tobacco smoking, water pollution, and air pollution.